2012
DOI: 10.1111/j.1467-8659.2012.03178.x
|View full text |Cite
|
Sign up to set email alerts
|

Mean Curvature Skeletons

Abstract: Figure 1: Given a watertight surface (a), the well-known medial axis transform (b) often produces too complex of a structure to be of practical use. Our skeletonization algorithm can produce intermediate meso-skeletons (c), which contain medial sheets where needed and curves where appropriate, while converging to a medially centered curve skeleton output (d). AbstractInspired by recent developments in contraction-based curve skeleton extraction, we formulate the skeletonization problem via mean curvature flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
203
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(208 citation statements)
references
References 35 publications
(68 reference statements)
1
203
0
4
Order By: Relevance
“…A native plane (a) cannot represent all structures of the placenta at once. Therefore, we use our segmentation method (b), correct the motion in this area using [3], project the placenta mask into the the resulting isotropically resolved volume (c), extract the mean curvature flow skeleton [10] (black lines in (d)), use the resulting points to support a curved surface plane (e) and visualize this plane with curved planar reformation [5] (f). The plane in (f) covers only relevant areas, hence gray value mapping can be adjusted automatically to emphasis placental structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A native plane (a) cannot represent all structures of the placenta at once. Therefore, we use our segmentation method (b), correct the motion in this area using [3], project the placenta mask into the the resulting isotropically resolved volume (c), extract the mean curvature flow skeleton [10] (black lines in (d)), use the resulting points to support a curved surface plane (e) and visualize this plane with curved planar reformation [5] (f). The plane in (f) covers only relevant areas, hence gray value mapping can be adjusted automatically to emphasis placental structures.…”
Section: Resultsmentioning
confidence: 99%
“…It is supported by a mean-curvature flow skeleton [10] generated from the triangulated polygonal mesh of the placenta segmentation and textured similar to curved planar reformation [5], see Figure 3. Although this part is not evaluated thoroughly, clinicians revealed that such a representation is potentially desirable since it compares well to a flattened placenta after birth.…”
Section: One Input Stackmentioning
confidence: 99%
“…This approach, although less robust than [17,23,11] presents heuristics for collapsing spurious branches and closing loops whenever two terminal nodes have intersecting maximal balls, which are beneficial for the resulting structure. A particularly notable example of point cloud based methods is the work of Huang et al [14], which allows to obtain high quality skeletons from raw and potentially incomplete scans by using the L1-median operator.…”
Section: Related Workmentioning
confidence: 99%
“…We refer to [15,19] for a qualitative comparison of the most representative methods based on this idea. A recent contraction-based method is [11] which is a robust skeletonization algorithm whose resulting skeletons are topology-preserving, usually well centered and smoother than previous similar methods.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation